An in-situ formable and fibrils-reinforced polysaccharide composite hydrogel by self-crosslinking with dual healing ability. (1st March 2018) - Ye, Bihua; Zhang, Shuyun; Li, Riwang; Li, Lihua; Lu, Lu; Zhou, Changren
Abstract: Novel in-situ formable and fibrils-reinforced polysaccharide-based composite hydrogels with dual healing ability were prepared by a facile, one-pot approach with maleilated chitosan (CS-MA) and thiol derivatised sodium alginate (SA-SH), via Michael addition reaction and ionic interaction. The unique fibrils network working as reinforcement fillers were attributed to the electrostatic interaction of CS-MA with SA-SH. This CS-MA/SA-SH composite hydrogel can self-heal cracks through dynamic disulfide exchange in 12 h at 37 °C without any external intervention. Noteworthy, fast healing ability inside hydrogels or with porous scaffolds within 1 min can be obtained via the introduction of calcium ions. Moreover, tunable shapes can also be obtained via dual cross-linking, providing advantages to optimize the fibrils-reinforced composite gels system for more biomedical applications. In addition, cell viability and proliferation showed that both of the gels before and after healing with Ca 2+ possessed good cytocompatibility. Graphical abstract: